Between no-fault and fault-based: Has Indonesia consistently adopted the fault-based divorce law system? - Hartini; Ari Hernawan; Dwi Haryati; Haniah Ilhami; Laras Susanti; Nur Yaumil Hikmah (Jurnal Hukum Novelty, 2025)
Introduction to the Problem: Under the Indonesian Marriage Law of 1974, the requirement of specific acceptable reasons for divorce underscores the adoption of a fault-based divorce system. However, of the Law also includes “continuous disputes and endless quarrels between the spouses with no hope of reconciliation” as grounds for divorce provided by the Elucidation of Article 39 paragraph (2) letter f, which mirrors the Western no-fault-based divorce concept of irreconcilable differences. This apparent contradiction is intriguing for a comprehensive analysis of which divorce system Indonesia aligns with. Purpose/Study Objectives: This article evaluates the contradiction between Indonesia’s fault-based divorce system and the existence of grounds for divorce, which include “persistent disputes and endless quarrels between the spouses with no hope of reconciliation.” This evaluation aims to confirm whether Indonesia has consistently adhered to the fault-based divorce law system. Design/Methodology/Approach: This article utilizes normative juridical research by examining secondary data as the primary source. The research began with identifying legal principles governing divorce, followed by analyzing the historical development of regulations and legal considerations in judicial decisions. The data were qualitatively analyzed using conceptual, statutory, case-based approaches to provide a critical perspective. Findings: This article reveals that the grounds of “persistent disputes with no hope of reconciliation” first appeared in 1933 under the Indonesian Christian Marriage Ordinance of 1933 under the terminology of onheelbare tweespalt. It was then adopted by the Marriage Law of 1974. Initially, all divorce reasons had to be grounded in the fulfilment of "persistent disputes with no hope of reconciliation," requiring the determination of the party most responsible for the breakdown of the marriage. However, this article concludes that there has been a gradual shift from necessitating identifying fault in "persistent disputes with no hope of reconciliation" to simply recognizing the marriage's breakdown without attributing blame. This ground is now independently sufficient to establish an irreparable breakdown of the marriage. Paper Type: Research Article.